A Decade of Inaction in the SADC region? - disaster risk data gaps and inconsistencies on the Sendai Framework Monitor. (December 2022) - Khoza, Sizwile; van Niekerk, Dewald; Nemakonde, Livhuwani David
Abstract: This paper considered the disaster risk-related data from the primary databases used for official progress reporting on the Sendai Framework Monitor (SFM), and the 2030 Agenda for Sustainable Development - United Nations Statistics Division database. We conducted a comparative study to analyse the available data and track progress on Target E: Indicator E1. Findings show that the SFM had less than 50% of SADC countries reporting on Target E, indicating little progress towards reporting the region's adoption and implementation of national DRR strategies. There are concerning inconsistencies and gaps that limit the applicability of risk data in development decisions. Highlights: Concerning shortcomings of the status of disaster risk data collection and reporting in Southern Africa. Inconsistencies and gaps that limit the applicability of risk data in development decisions. Weak integration and poor coordination of government institutions' data collection and reporting functions. SADC countries need to improve investment in disaster risk data collection and information management. Disaster risk data should form the core of decision-making to reduce disaster risk and drive sustainable development.